Easy, take your problem,
-5(a-6)+2a
Multiply the 5.
-5a+30+2a
Then just add apples and oranges.
-5a+2a= -3a.
Making your equation -3a+30.
Answer:
C) 6
Step-by-step explanation:
Alternate interior angles are congruent meaning that they are equal to each other sp 18x+2=110 is simplified to 18x=108. Then divide by 18 to get x equal to 6. Hope this helped and post more :)
Cubic inch.
Proszę.
Myślę że pomoglem.
Part A. Lest fin the zeros of our function first:
Step 1. Set the right side of the function equal to 0:
![0=-x^2-7x+30](https://tex.z-dn.net/?f=0%3D-x%5E2-7x%2B30)
Step 2. Multiply both sides of the equation by -1
![(-1)(-x^2-7x+30)=0(-1)](https://tex.z-dn.net/?f=%28-1%29%28-x%5E2-7x%2B30%29%3D0%28-1%29)
Step 3. Factor the left side:
Step 4. Set each factor equal to 0 and solve for
![x](https://tex.z-dn.net/?f=x)
:
![x+10=0](https://tex.z-dn.net/?f=x%2B10%3D0)
and
![x-3=0](https://tex.z-dn.net/?f=x-3%3D0)
![x=-10](https://tex.z-dn.net/?f=x%3D-10)
and
![x=3](https://tex.z-dn.net/?f=x%3D3)
Since distances can't be negative, the zero of our function is
![x=3](https://tex.z-dn.net/?f=x%3D3)
.
<span>We can conclude that the zero </span>
represents that when the horizontal distance of the diver is 3 ft, he is is in the surface of the pool. In other words, his vertical distance is zero.
Part B. To factor our quadratic equation
![9x^2+3x-2=0](https://tex.z-dn.net/?f=9x%5E2%2B3x-2%3D0)
, we are going to use the method for simple cases because
![a \neq 0](https://tex.z-dn.net/?f=a%20%5Cneq%200)
:
Step 1. Find tow numbers whose product is
![ac](https://tex.z-dn.net/?f=ac)
and its sum is
![b](https://tex.z-dn.net/?f=b)
:
We know form our quadratic that
![a=9](https://tex.z-dn.net/?f=a%3D9)
,
![b=3](https://tex.z-dn.net/?f=b%3D3)
, and
![c=-2](https://tex.z-dn.net/?f=c%3D-2)
, so
![ac=9(-2)=-18](https://tex.z-dn.net/?f=ac%3D9%28-2%29%3D-18)
.
We want tow numbers that multiply together to make -18, and add up to 3.
Those number are 6 and -3.
![(6)(-3)=-18](https://tex.z-dn.net/?f=%286%29%28-3%29%3D-18)
and
Step 2. Rewrite the middle term
![3x](https://tex.z-dn.net/?f=3x)
using those numbers:
Step 3. Factor the expression:
![(9x^2+6x)-(3x+2)=0](https://tex.z-dn.net/?f=%289x%5E2%2B6x%29-%283x%2B2%29%3D0)
![3x(3x+2)-(3x+2)=0](https://tex.z-dn.net/?f=3x%283x%2B2%29-%283x%2B2%29%3D0)
![(3x+2)(3x-1)=0](https://tex.z-dn.net/?f=%283x%2B2%29%283x-1%29%3D0)
Answer:
it's equal=
Step-by-step explanation:
5 divided by 8 = .625, 25 divided by 40= .625